P0818IMPROVING MORTALITY TRENDS FOR PATIENTS WITH CHRONIC KIDNEY DISEASE IN THE IRISH HEALTH SYSTEM: THE IRISH KIDNEY DISEASE SURVEILLANCE SYSTEM (IKDSS). (6th June 2020) - Laird, Matthew; Alheyali, Raihan; Browne, Leonard; Plant, Liam; Walsh, Cathal; Austin, Stack
Abstract: Background and Aims: It is unclear whether targeted efforts for the treatment of chronic kidney disease (CKD) has led to a sustained reduction in mortality rates. We examined annual trends in mortality for patients with and without CKD in the Irish health system. Method: We utilised data from the Irish Kidney Disease Surveillance System (IKDSS) to explore 1-year mortality rates among patients with and without CKD in the health system. The principal data sources included; regional laboratory information systems; dialysis registers; and mortality data files from the national Central Statistics Office (CSO). We created multi-annual cohorts of patients, age > 18 years with one or more serum creatinine values who received healthcare within the Irish health system from 2008 to 2012. Serum creatinine values (first test in fiscal year) were used to calculate glomerular filtration rate (eGFR) and CKD was defined as GFR < 60ml/min/1.73m. Mortality data were available from the national mortality files with vital status up to December 31 st 2013. Age standardised death rates were determined for the Irish population (IRE) and the European Standard Population (ESP) (standardised to the age distribution of a standard European population in 2012. Comparisons were conducted using segmented linear regression. Results: We included 351, 223 adult individuals between 2008 and 2012. Age standardised mortality rates (EU) were more than 2-fold higher for patients with CKD than without, P<0.001 . From 2008-2012, age-standardised mortality rates decreased significantly in patients with CKD from a peak of 47.7 to 31 per 1000 person-years, P for trend=p=0.012, and from a peak of 17.8 to 15.5 per 1000 person-years in patients without CKD, P= 0.006. Mortality rates for men were significantly higher than for women in patients with and without CKD, but the pattern of improvement was similar for both sexes. These patterns were replicated when comparisons were made using Irish standard age distribution. Conclusion: Mortality rates among CKD patients have declined in the Irish population from 2008 to 2012 in both men and women. The processes and interventions that have led to these reductions need further exploration. Figure 1. (a) Crude and age standardised mortality rates (b-c) of those with and without CKD in the Irish Health System between 2008-2012 .